1991
DOI: 10.1007/bf00436374
|View full text |Cite
|
Sign up to set email alerts
|

Studies on clinical signs and haematological alterations in pneumonic aspergillosis due to Aspergillus flavus in Japanese quail

Abstract: Intratracheal inoculation of 2-week old quail chicks with Aspergillus flavus spores resulted in the development of clinical signs within 24 h of infection. These were characterized by dullness, depression, anorexia, accelerated breathing, gasping and prostration leading to death. These signs continued up to 7 days followed by considerable decrease in the intensity of the symptoms as well as number of birds showing clinical signs. Mortality occurred primarily in the first week with a majority of the birds dying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Gross postmortem examination of the goslings showed variously sized yellowish-white nodules scattered throughout the lungs and within the air sacs, in accordance with observations made on other avian species (Hawkey et al, 1984;Reece et al, 1986;Ulloa et al, 1987;Bowes, 1990;Flach et al, 1990;Pandita et al, 1991;Machin et al, 1993). In some cases, a large portion of the lung lobes was obliterated by large coalesced granulomas, as observed previously in Stellar's jays (Machin et al, 1993), turkeys (Dyar et al, 1984) and chickens (Chaudhary and Singh, 1983).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Gross postmortem examination of the goslings showed variously sized yellowish-white nodules scattered throughout the lungs and within the air sacs, in accordance with observations made on other avian species (Hawkey et al, 1984;Reece et al, 1986;Ulloa et al, 1987;Bowes, 1990;Flach et al, 1990;Pandita et al, 1991;Machin et al, 1993). In some cases, a large portion of the lung lobes was obliterated by large coalesced granulomas, as observed previously in Stellar's jays (Machin et al, 1993), turkeys (Dyar et al, 1984) and chickens (Chaudhary and Singh, 1983).…”
Section: Discussionsupporting
confidence: 85%
“…It is most likely that the cause of death of the goslings was these pulmonary lesions. Likewise, it has been reported that the death of birds affected by aspergillosis was due to respiratory failure because of affection of a large portion of the lung parenchyma (Okoye and Okeke, 1986;Pandita et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical CBC results are a leucocytosis with heterophilia, lymphopenia, and monocytosis, and a non-regenerative anemia (depression anemia), especially in chronic disease cases. 17,[72][73][74] Therefore, a heterophilic leucocytosis may indicate a current infection and subsequent involvement of the bird's immune system, but one should always interpret hematology results in combination with clinical findings and other diagnostic test results. Additional hematologic testing will allow one to monitor the patient's treatment response.…”
Section: Hematologymentioning
confidence: 99%